AN OVERVIEW OF STUDIES ON FINANCIAL EDUCATION IN EDUCATIONAL INSTITUTIONS IN BRAZIL: AN INTEGRATIVE LITERATURE REVIEW (CIPEEX, 2024)
EXPLORING THE COMPLEXITY OF THE FINANCIAL SITUATION IN BRAZIL, WE HIGHLIGHT THE CRUCIAL IMPORTANCE OF FINANCIAL EDUCATION (FE) AND ITS RELATIONSHIP WITH THE INCREASE IN INDEBTEDNESS AND DEFAULT, CONTRASTING IT WITH A RELEVANT FACT OF THE COVID-19 PANDEMIC THROUGH AN INTEGRATIVE WAY OF LOOKING AT THE LITERATURE. THE STUDY OF FINANCE, OFTEN MISTAKENLY ASSOCIATED EXCLUSIVELY WITH MATHEMATICS AND CONSIDERED RELEVANT ONLY TO THOSE WITH SUBSTANTIAL RESOURCES, IS ACTUALLY A COMPREHENSIVE FIELD THAT GOES BEYOND SIMPLY SAVING MONEY. FE IS ESSENTIAL FOR GUARANTEEING A PROMISING FUTURE, QUALITY OF LIFE AND SECURITY IN THE FACE OF UNFORESEEN EVENTS, IMPACTING ALL AREAS OF LIFE, DEVELOPING A CRITICAL MINDSET IN STUDENTS AND EMPOWERING THEM TO CONSCIOUSLY NAVIGATE THIS SOCIAL DYNAMIC IN AN ETHICAL AND SUSTAINABLE MANNER. INDEBTEDNESS REFERS TO THE ACQUISITION OF FINANCIAL OBLIGATIONS, WHILE DEFAULT STEMS FROM A LACK OF FINANCIAL MANAGEMENT, NEGATIVELY IMPACTING THE SOCIAL AND FAMILY SPHERES. IN THE BRAZILIAN CONTEXT, THE INDISCRIMINATE USE OF LOANS AND CREDIT LINES, WITHOUT PROPER UNDERSTANDING, CONTRIBUTES TO HIGH INTEREST RATES AND REFLECTS A FINANCIAL RISK PROFILE IN THE CULTURE OF INDEBTEDNESS. IN ADDITION, THE COVID-19 PANDEMIC, TOGETHER WITH INFLATION AND HIGH INTEREST RATES, HAS A SUBSTANTIAL IMPACT ON GROWING INDEBTEDNESS AND DEFAULT. THE RESEARCH AIMS TO UNDERSTAND THE PERCEPTION OF PRIMARY, SECONDARY AND HIGHER EDUCATION STUDENTS ABOUT FE IN THE EDUCATIONAL ENVIRONMENT. THE METHOD EMPLOYED IS AN INTEGRATIVE LITERATURE REVIEW, WITH A BIBLIOGRAPHIC FOCUS ON THE CAPES, SCIELO, SPELL AND GOOGLE SCHOLAR DATABASES. THE EXPLORATORY RESEARCH SELECTED THE BEST RESULTS QUALITATIVELY, USING THE BOOLEAN OPERATOR "AND" TO UNDERSTAND AND COMPARE KNOWLEDGE ON THE SUBJECT. THE PERIOD SELECTED FROM 2018 TO 2023 OFFERS RECENT INSIGHTS, USING THE PICO PROTOCOL FOR SPECIFIC SELECTION OF POPULATION, INTEREST AND SIMILAR CONTEXTS. THE RESULTS BASED ON ARTICLES FROM DIFFERENT QUALIS CLASSIFICATIONS PROVIDE THE INCLUSION OF 16 JOURNALS. IN ELEMENTARY SCHOOL, THE ILLUSION OF CONSUMERISM IS EVIDENCED, INDICATING THE NEED FOR A BROADER DISCUSSION ON FE. IN HIGH SCHOOL, THE MAJORITY OF STUDIES EMPHASIZE THE IMPORTANCE OF FE FOR PROFESSIONAL DEVELOPMENT AND MAKING INFORMED FINANCIAL DECISIONS, ALTHOUGH THERE ARE DIFFERENCES IN STUDENTS' LEVEL OF KNOWLEDGE. IN HIGHER EDUCATION, THE RELATIONSHIP BETWEEN MATHEMATICS AND THE IMPORTANCE OF FE AS A CROSS-CUTTING THEME ARE HIGHLIGHTED. HOWEVER, THE IMPORTANCE OF FE IS JUSTIFIED BY THE CHALLENGES FACED BY SOCIETY, ESPECIALLY THE INDEBTEDNESS RESULTING FROM UNBRIDLED CONSUMPTION. IN ADDITION, FE IN EVERYDAY LIFE IS ASSOCIATED WITH RATIONAL AND EMOTIONAL ASPECTS, PROMOTING REFLECTION IN PURCHASING DECISIONS. GIVEN THE SCOPE OF THE STUDY, THE NEED FOR FURTHER RESEARCH IN DIFFERENT CITIES AND STATES IS EVIDENT, IN ORDER TO PROVIDE VALUABLE FINDINGS TO SUPPORT EDUCATIONAL POLICIES AIMED AT PROMOTING FINANCIAL LITERACY AMONG YOUNG PEOPLE AND ADULTS.
Keywords: Student; Financial Education; Indebtedness; School